Integrasi Islam, Sains dan Level Integrasi - Bella Putri Sabilla; Canasta Rafanza Faris; Alfina Wildatul Fitriyah (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
Islam, the religion which is in accordance with human nature, Sharia not only encourage people to study science and technology, but also build a civilization, even set his people to survive and save both the world and in the hereafter. Furthermore that all activities include reviewing and developing science and technology can be a valuable worship even it can be a fight value on the side of God. At issue until now, is still the perception in the wider society, that religion and science are two entities that cannot be met. Both have their respective areas, separated from each other, both in terms of formal object-material, research methods, criteria of truth, the role played by scientists. This is due to the notion that science and religion both have different ways of approach, experience, and these differences are a source of debate. The problem that arises now is how to do the integration between science and religion through Islamic religious education, and what kind of integration to be conducted?